PENGARUH INDEPENDENSI, KEAHLIAN PROFESIONAL, PENGALAMAN KERJA, DAN TINGKAT PENDIDIKAN PADA KINERJA PENGAWAS KOPERASI - Murtini, Ni Nengah; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 20 No 2 (2017), 2017)
Duties, powers and responsibilities of supervisors cooperatives have an important role to the survival of the cooperative in accordance with the law on cooperatives number 25 of 1992. The development of cooperatives in Karangasem R egency is increasing every year but the quality still need to be developed more intensively because there are cooperatives that do not implement the annual members meeting. This study focused on supervisors working in cooperatives in the District of Rendang because a preliminary survey in January 2017 showed that only 56 percent of the cooperatives in the District Rendang Karangasem regency which perform annual members meeting. The purpose of this study is to determine the influence of independence, professional skills, work experience, and level of education on the performance of cooperative supervisors in the District Rendang Karangasem. This study took the sample of the overall supervisory cooperatives in Rendang District Karangasem based on non-probability sampling method with saturated sample technique and use 150 samples of supervisors. Data collection was done by survey method. The analysis technique used in this research is multiple linear regression analysis. Based on the results of the analysis shows that independence, professional skills, work experience and educational level has significantly positive affect on the performance of cooperative supervisors in Rendang district, Karangasem regency. This indicates that the higher independence, professional skills, work experience and level of education will make higher the performance of the supervisor.